The effect of metal distribution on the luminescence properties of mixed-lanthanide metal–organic frameworks. Issue 7 (26th January 2018) - Cadman, Laura K.; Mahon, Mary F.; Burrows, Andrew D.
Abstract : The MOFs [Ln(Hodip)(H2 O)]· n H2 O (H4 odip = 5, 5′-oxydiisophthalic acid) have been prepared together with mixed-metal analogues, and the distribution of the metal centres has been shown to affect the luminescence properties. Abstract : A series of lanthanide metal–organic frameworks (MOFs) of the general formula [Ln(Hodip)(H2 O)]· n H2 O (Sm, 1 ; Eu, 2 ; Gd, 3 ; Tb, 4 ; Dy, 5 ; Er, 6 ; H4 odip = 5, 5′-oxydiisophthalic acid) have been prepared and shown crystallographically to have isostructural three-dimensional frameworks. The fluorescence emission spectra of the europium compound2, which is red, and the terbium compound4, which is green, show characteristic peaks for transitions involving the metal centres, whereas that for the gadolinium compound3 is dominated by transitions involving Hodip. Using a 1 : 1 : 1 mixture of europium, gadolinium and terbium nitrates in the synthesis resulted in the mixed-metal MOF [Gd0.17 Tb0.19 Eu0.64 (Hodip)(H2 O)]· n H2 O7, for which the ratio of the metal ions was determined using EDX spectroscopy. The fluorescence emission spectrum of7 is dominated by europium emission bands reflecting the higher proportion of Eu 3+ centres and quenching of the terbium fluorescence by metal-to-metal energy transfer. A series of core–shell MOF materials based on the Ln(Hodip)(H2 O) framework have been prepared in order to isolate the lanthanides in different domains within the crystals. The emission spectra for materials with Gd@Tb@Eu (8 ) and Tb@Eu@Gd (9 ) are dominated by terbium emissions, suggesting that physical separation from europium suppresses quenching. In contrast, the material with Eu@Gd@Tb (10 ) shows only broad ligand bands and europium emissions. This confirms that core–shell MOFs have different fluorescence properties to simple mixed-metal MOFs, demonstrating that the spatial distribution of the metals within a mixed-lanthanide MOF affects the fluorescence behaviour.